Answer:
1/12
Step-by-step explanation:
When you are doing probability with multiple things at once you have to multiply the probabilities of each asked number from each object together to get the probability of them both landing on those numbers
Answer:
f(x)=x+3
Step-by-step explanation:
hope this helps
Answer: He has planted 2/3 and there is 1/3 left to plant.
Explanation: You need to add your fractions together, because each of those is a section of the garden and you need the total of how much of the garden he has planted.
This isn’t too difficult because the denominators are the same.
5/12 + 3/12 = 8/12
It is 8/12 because since the denominators are the same, you just need to add the numerators. Imagine you have a pie that’s cut into 12 pieces, and you and your friends take 5, and then your family takes 3. How many or gone now? 8 pieces. From how many pieces? 12 pieces. So 8/12 pieces are gone.
So Peter has planted 8/12 of his garden. This however, can be simplified, because both of those numbers divide by 4.
8/4 = 2
12/4 = 3
So 8 is now 2, and 12 is now 3.
This is now 2/3.
If there is 2/3 gone, you need to figure out how much is left to get you to 1.
In this instance, 1 can be rewritten as 3/3, because 3 divided by 3 is 1.
In order to get from 2/3 to 1, you need to add 1/3, one more third to the two thirds you already have.
This means Peter has 1/3 left to plant.
Hope this helps :)
Answer:
1.) He still owes $100 of debt
2.) 1 rose would be .75 cents and 1 carnation would be .90 cents
3.) C 8 and 3/8
Step by Step explanation
(/ means divided by in the first 2 equations but / in the last question is for the fractions.)
1.) _(1,500 / 3 =500. 1,500 - 500 =1,000 / 5 =200 x 3 =600. 700 - 600 =$100)
2.)_(1.50/2 =.75 cents. 2.70/3 =.90 cents.)
3.) i first added the fractions ( i equalized them) then i added the whole numbers (the u in the equation was to separate the whole num. and fraction )
Before i equalized it: (6u3/4 + 1u1/8 = 7u1/8 + 1/8 = 8u3/8)
After i equalized it: (6u6/8 + 1u1/8 = 7u1/8 + 1/8 = 8u3/8)
Answer:
f'(9) = 6
Step-by-step explanation:
f(x) = 6x+7
The derivative is
f'(x) = 6
Evaluated at x=9
f'(9) = 6